STUDI PENGARUH PROSES MANUFAKTUR KOMPOSIT BERMATRIK EPOKSI TERHADAP KEKUATAN TARIK DAN IMPAK PADA KOMPOSIT HYBRID BERPENGUAT SERBUK KAYU ALBASIA DAN SERAT GELAS - Fajar Nugroho (Institut Teknologi Dirgantara Adisutjipto, 2016)
A composite material is very efficient to use at a structure which needs a combination between strength and stiffness and light weight. The advantage of composite material compared to a metal is corrosion resistance, accessible, and reasonable price. This study aims to determine the tensile and impact strength composites of the epoxy matrix composite reinforced by glass fiber and albsia sawdust.The composites were made using variations of stirring time 15 minutes and 30 minutes with a stirring speed of 658 rpm and 858 rpm. The composite were made using variations of the drying temperatures 40ºC, 50ºC, 60ºC, 70ºC, and the room temperature. The reinforced materials is used albasia sawdust and woven glass fiber. The matrix was Epoxy Resin Bakelite EPR 174 and Epoxy Hardener V-140. The methodology for making the composite test specimens particles was hand lay-up (open mold). The highest tensile strength testing on a composite was 37.92 MPa with a stirring time of 30 minutes and 858 rpm stirring rotation. For the impact testing, the highest visible impact at 0.0024 J/mm² in the composite with a stirring time of 15 minutes and 858 rpm stirring rotation. Through this test, it was obtained the highest tensile strength of 43.03 MPa in the composite with 50ºC drying temperature variation. Meanwhile, the composites with 60ºC drying temperature variation had the highest impact strength with a value of 0.0037 J/mm². The composite material composition and morphology of the fracture were analyzed by SEM observation.